Solid electrolyte for secondary battery, electrode for secondary battery, all-solid-state secondary battery, and method for manufacturing all-solid-state secondary battery

By using an amorphous solid electrolyte containing alkali metal oxide and silicon oxide and composite coating process, the problem of deterioration of battery characteristics caused by high-temperature firing is solved, the excellent adhesion and density between the electrode and the solid electrolyte are achieved, and the overall performance of the all-solid sodium secondary battery is improved.

CN119895614APending Publication Date: 2025-04-25NIPPON ELECTRIC GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063374.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-16
Filing Date
2023-12-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When using Beta alumina solid electrolyte to prepare all-solid sodium secondary batteries, high-temperature firing may lead to the reaction between the electrode active substance and the solid electrolyte, deteriorating the battery characteristics, and limiting the optional electrode active substance materials.

Method used

An amorphous solid electrolyte containing alkali metal oxide and silicon oxide is used to prepare electrodes through the composite material coating process and the heat treatment process to avoid high-temperature firing, so as to achieve excellent adhesion and densification between the electrode and the solid electrolyte.

Benefits of technology

It achieves excellent adhesion and density between the electrode and the solid electrolyte without high temperature firing, and improves the overall characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895614A_ABST
    Figure CN119895614A_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte which has excellent adhesion to an electrode and is densified even without being fired at high temperatures, and which can achieve good battery characteristics. The solid electrolyte for a sodium ion secondary battery is characterized by containing an alkali metal oxide and silicon oxide and being amorphous.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte for a secondary battery, an electrode for a secondary battery, an all-solid-state secondary battery and a method for manufacturing the all-solid-state secondary battery, which are used for power storage devices such as an all-solid-state sodium ion secondary battery. Background Art

[0002] Lithium-ion secondary batteries have established their position as high-capacity and lightweight power sources that are indispensable for mobile devices, electric vehicles, etc. However, in existing lithium-ion secondary batteries, flammable organic electrolytes are mainly used as electrolytes, so there is a concern about the danger of fire. As a solution to this problem, people are promoting the development of lithium-ion all-solid-state batteries that use solid electrolytes instead of organic electrolytes (for example, see Patent Document 1).

[0003] However, lithium has the risk of rising global raw material prices. Therefore, sodium has attracted attention as a material to replace lithium, and beta alumina-based solid electrolytes such as β-alumina and β″-alumina are used as solid electrolytes.

[0004] Patent Document 1 discloses an all-solid-state sodium ion secondary battery using a Beta alumina-based solid electrolyte such as β-alumina or β″-alumina as a solid electrolyte.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: International Publication No. WO2018 / 225494. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] When the conventional Beta alumina solid electrolyte is used in all-solid-state sodium secondary batteries, the electrode active material is mixed with the solid electrolyte and fired at high temperature to prepare a dense electrode with excellent adhesion to the electrode. However, there is a problem that during firing, a reaction may occur between the electrode active material and the solid electrolyte, resulting in deterioration of battery characteristics, so the materials of the electrode active material that can be selected are limited.

[0010] In view of the above circumstances, an object of the present invention is to provide a solid electrolyte which can have excellent adhesion to an electrode and can be densified even without being fired at a high temperature, thereby achieving good battery characteristics.

[0011] Technical means of solving problems

[0012] Each method for solving the above-mentioned problems will be described.

[0013] The solid electrolyte for sodium ion secondary batteries according to the first aspect of the present invention is characterized by containing an alkali metal oxide and silicon oxide and being amorphous.

[0014] The solid electrolyte for sodium ion secondary batteries according to the second aspect of the present invention preferably contains 5 to 70% of Na2O and 15 to 90% of SiO2 in terms of mol% in the first aspect.

[0015] The solid electrolyte for sodium ion secondary batteries according to the third aspect of the present invention is preferably used in an all-solid-state sodium ion secondary battery in the first or second aspect.

[0016] The sodium ion secondary battery electrode according to the fourth aspect of the present invention is characterized by comprising the solid electrolyte for sodium ion secondary batteries configured according to any one of the first to third aspects and an electrode active material.

[0017] The sodium ion secondary battery electrode of the fifth aspect of the present invention is preferably, in the fourth aspect, further comprising at least one sodium ion conductive crystal selected from the group consisting of β-alumina, β″-alumina and NASICON crystal.

[0018] The sodium ion secondary battery electrode according to aspect 6 of the present invention is preferably such that, in aspect 4 or 5, the solid electrolyte for sodium ion secondary batteries is contained inside the sodium ion secondary battery electrode.

[0019] In the sodium ion secondary battery electrode according to aspect 7 of the present invention, in aspect 4 or 5, it is preferred that the solid electrolyte for a sodium ion secondary battery is formed on one main surface of the sodium ion secondary battery electrode.

[0020] The sodium ion secondary battery electrode according to aspect 8 of the present invention may be any one of aspects 4 to 7, wherein the electrode active material is a negative electrode active material.

[0021] The electrode for sodium ion secondary battery of mode 9 of the present invention is preferably that, in mode 8, the negative electrode active material contains: at least one metal crystal selected from Sn, Bi, Pb, P and Sb, an alloy crystal containing at least one selected from Sn, Bi, Pb, P and Sb, glass containing at least one selected from Sn, Bi and Sb, hard carbon or soft carbon.

[0022] The sodium ion secondary battery electrode according to aspect 10 of the present invention may be any one of aspects 4 to 7, wherein the electrode active material is a positive electrode active material.

[0023] The electrode for a sodium ion secondary battery of embodiment 11 of the present invention is preferably that, in embodiment 10, the positive electrode active material contains (i) at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr, (ii) an element consisting of Na and (iii) an element consisting of O.

[0024] The sodium ion secondary battery electrode of aspect 12 of the present invention is preferably such that, in aspect 10 or 11, the positive electrode active material contains a compound having the general formula Na x M y P2O z (1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, M is at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr).

[0025] In the sodium ion secondary battery electrode according to aspect 13 of the present invention, in any one of aspects 10 to 12, it is preferred that the positive electrode active material further contains an amorphous phase.

[0026] The sodium ion secondary battery electrode according to aspect 14 of the present invention is preferably any one of aspects 4 to 13, further comprising a conductive auxiliary agent.

[0027] The sodium ion secondary battery electrode of aspect 15 of the present invention, in any one of aspects 4 to 14, preferably contains, by mass%, 70% to 99% of the electrode active material and 1% to 20% of the solid electrolyte for sodium ion secondary batteries.

[0028] A sodium ion secondary battery according to a sixteenth aspect of the present invention is characterized by comprising an electrode for a sodium ion secondary battery configured according to any one of aspects four to fifteen.

[0029] A sodium ion secondary battery according to aspect 17 of the present invention is characterized by comprising a solid electrolyte layer containing the solid electrolyte for a sodium ion secondary battery constructed according to any one of aspects 1 to 3.

[0030] The method for manufacturing a sodium ion secondary battery of mode 18 of the present invention is characterized in that it includes: a composite material coating step, coating an electrode composite material containing an electrode active material and water glass on the main surface of a diaphragm layer containing β-alumina, β″-alumina, and NASICON crystals; and a heat treatment step, after coating, performing heat treatment at a temperature below 200°C.

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a solid electrolyte which has excellent adhesion to an electrode and can be made dense, thereby achieving good battery characteristics, even without being fired at a high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic cross-sectional view showing one embodiment of the electrode for a sodium ion secondary battery of the present invention.

[0034] Figure 2 This is a schematic cross-sectional view showing another embodiment of the electrode for a sodium ion secondary battery of the present invention.

[0035] Figure 3 This is a cross-sectional SEM image of an electrode formed on a separator layer in Example 1 of the electrode for a sodium ion secondary battery of the present invention.

[0036] Figure 4 This is a diagram showing the first charge and discharge curve of the test cell prepared in Example 1 of the electrode for a sodium ion secondary battery of the present invention. DETAILED DESCRIPTION

[0037] The solid electrolyte for sodium ion secondary battery of the present invention is characterized in that it contains alkali metal oxide and silicon oxide and is amorphous. As a specific composition, it can be cited that it contains 5 to 70% Na2O and 15 to 90% SiO2 in mol%. The following explains the reason for limiting the composition as described above.

[0038] Alkali metal oxides are components used to impart ion conductivity. Examples of alkali metal oxides include Li2O, Na2O, and K2O. Among them, Na2O is preferred because it can constitute sodium ions that move during charge and discharge of a sodium ion secondary battery. The content of Na2O is preferably 5 to 70%, 10 to 60%, and particularly preferably 15 to 50%. When Na2O is too little, it is difficult to obtain the above-mentioned effects. On the other hand, when Na2O is too much, excess sodium forms compounds that do not contribute to ion conductivity, so the ion conductivity of the solid electrolyte is easily reduced.

[0039] Silicon oxide (SiO2) is a skeleton component that forms an ion conduction path composed of a three-dimensional network of Si-O-Si bonds. Furthermore, since it is amorphous, the above-mentioned three-dimensional network is randomly constructed compared to the case of crystals, so a larger continuous ion conduction path can be formed, which can further improve the ion conductivity. In addition, when an alkali metal oxide is contained, non-crosslinked oxygen is formed, so the size of the ion conduction path becomes further larger, which can further improve the ion conductivity. The content of SiO2 is preferably 5-70%, 10-60%, and particularly preferably 15-50%. When SiO2 is too little, it is difficult to maintain the amorphous three-dimensional network, and the ion conductivity is easily reduced. On the other hand, when SiO2 is too much, the non-crosslinked oxygen decreases, so the ion conductivity is easily reduced.

[0040] The solid electrolyte for sodium ion secondary batteries of the present invention can be produced by heat-treating an aqueous solution of lithium silicate, sodium silicate or potassium silicate at 200° C. or less to remove water.

[0041] The electrode for sodium ion secondary battery of the present invention is characterized in that it comprises the solid electrolyte for sodium ion secondary battery and electrode active material. The electrodes include positive electrode and negative electrode, the electrode active material contained in the negative electrode is negative electrode active material, and the electrode active material contained in the positive electrode is positive electrode active material.

[0042] The negative electrode active material is not particularly limited as long as it is a material that absorbs sodium during charging and releases sodium during discharging. For example, carbon electrode materials such as hard carbon and soft carbon can be used. The carbon electrode material is preferably hard carbon. Of course, the negative electrode active material may also include: metal crystals that can absorb and release sodium selected from at least one of Sn, Bi, Pb, P and Sb, alloy crystals containing at least one selected from Sn, Bi, Pb, P and Sb, and glass containing at least one selected from Sn, Bi and Sb. In addition, the negative electrode layer is preferably not a negative electrode layer composed of a single phase of metallic sodium.

[0043] The positive electrode active material is not particularly limited as long as it is a material that releases sodium during charging and absorbs sodium during discharging. For example, a positive electrode active material containing (i) at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr, (ii) an element consisting of Na, and (iii) an element consisting of O can be used. Among them, a positive electrode active material containing a general formula Na x M y P2O z The positive electrode active material is a crystalline positive electrode active material represented by (1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, M is at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr). In addition, the positive electrode active material preferably further contains an amorphous phase.

[0044] The ratio of each material in the electrode can be, for example, 70% to 99% of the electrode active material and 1% to 20% of the solid electrolyte for sodium ion secondary batteries in terms of mass %.

[0045] The electrode may further include at least one sodium ion conductive crystal selected from β-alumina, β″-alumina and NASICON crystal, and a conductive auxiliary agent.

[0046] At least one sodium ion conductive crystal selected from β-alumina, β″-alumina and NASICON crystal can further improve the ion conductivity of the electrode for sodium ion secondary battery. The preferred content of the sodium ion conductive crystal is 0% to 15% by mass, and more preferably 1% to 12%.

[0047] The conductive aid is a component added to achieve high capacity and high rate of the electrode. As the conductive aid, for example, conductive carbon can be used. As conductive carbon, for example, acetylene black, carbon black, Ketjen black, vapor-phase carbon fiber conductive aid (VGCF), carbon nanotubes, etc. can be cited. In addition, as the conductive aid, metal powders such as Ni powder, Cu powder, and Ag powder can also be cited. The preferred content of the conductive aid is 0% to 5% by mass, and more preferably 1% to 3%.

[0048] The following, Figure 1 A method for forming the electrode 1 including the electrode active material and the solid electrolyte for a sodium ion secondary battery of the present invention will be described.

[0049] First, the electrode active material powder is mixed with an aqueous solution of lithium silicate, sodium silicate, and potassium silicate to prepare a slurry. Next, the slurry is applied to the main surface of the diaphragm layer 4 containing sodium ion conductive crystals such as β-alumina, β″-alumina, and NASICON crystals. Instead of the diaphragm layer 4, the slurry can also be applied to the main surface of a collector (collector foil) composed of a metal such as Al, which is not shown. In addition, the diaphragm layer 4 is provided between the positive electrode and the negative electrode, and is a layer with high ion conductivity but low electron conductivity. Next, heat treatment is performed at a temperature below 200°C to remove moisture, thereby obtaining an electrode 1 formed on the diaphragm layer 4 and the collector. The obtained electrode 1 is as shown in Figure 1 As shown, it has a structure in which an electrode active material 2 and a solid electrolyte 3 for a sodium ion secondary battery are dispersed.

[0050] The atmosphere for the heat treatment is not particularly limited, and the heat treatment may be carried out in an atmospheric atmosphere, an inactive atmosphere, or a vacuum atmosphere. If the electrode active material is easily degraded by oxidation, the heat treatment may also be carried out in a reducing atmosphere containing H2. The heat treatment temperature is below 200°C, preferably below 180°C, and more preferably below 160°C. The lower limit of the heat treatment temperature is not particularly limited, but is preferably above 0°C, more preferably above 10°C, further preferably above 20°C, and particularly preferably above 30°C.

[0051] As another embodiment, Figure 2 As shown, an electrode 11 for a sodium ion secondary battery can be cited, wherein, in an electrode composed of an electrode core layer 12 and a solid electrolyte layer 13, a solid electrolyte layer 13 containing a solid electrolyte for a sodium ion secondary battery is formed on one main surface side (outer side) of the electrode core layer 12 containing an electrode active material. In this case, by arranging the solid electrolyte layer 13 between the electrode core layer 12 and the above-mentioned separator layer 14, the electrode core layer 12 and the separator layer 14 can be made to fit (closely adhere) with each other.

[0052] In the method for forming the electrode 11 of this embodiment, an electrode core layer 12 and a separator layer 14 are prepared, and an aqueous solution of lithium silicate, sodium silicate, and potassium silicate is applied to the surface of the electrode core layer 12. After the application, the applied surface is bonded to the main surface of the separator layer. After the bonding, a heat treatment is performed at a temperature below 200°C to remove moisture, thereby obtaining Figure 2 The electrode-separator layer complex is shown.

[0053] The method for forming the electrode core layer 12 is not particularly limited. For example, a slurry containing an electrode active material containing a binder can be applied to a collector foil not shown in the figure, and then dried to form the electrode core layer 12. Alternatively, the electrode active material powder can be press-formed to form the electrode core layer 12. In the case of insufficient strength, heat treatment can be performed at the sintering temperature of the active material after press-forming to form the electrode core layer 12. As another formation method, the electrode active material precursor powder containing glass can also be heated at a temperature above the crystallization temperature to form a crystallized glass obtained by precipitating electrode active material crystals from the glass. As described above, by firing only the electrode core layer 12, a battery component with good battery characteristics can be prepared without reacting with the diaphragm layer 14.

[0054] In addition, a collector layer can be provided on one main surface of the electrode. The material of the collector layer is not particularly limited, and metal materials such as aluminum, titanium, silver, copper, stainless steel or alloys thereof can be used. The above metal materials can be used alone or in combination. Among them, their alloys refer to alloys containing at least one of the above metals. The thickness of the collector layer is not particularly limited, and can be set in the range of 0.1 μm to 1000 μm.

[0055] The formation method of the current collector layer is not particularly limited, and for example, physical vapor methods such as evaporation or sputtering, chemical vapor methods such as thermal CVD, MOCVD, and plasma CVD can be cited. As other formation methods of the current collector layer, liquid phase film forming methods based on electroplating, sol-gel method, and spin coating can be cited. However, when the current collector layer is formed on the main surface of the electrode by sputtering, it is more preferred because of its excellent adhesion.

[0056] Example

[0057] Hereinafter, the present invention will be described in detail based on examples, but the present invention is not limited to the following examples.

[0058] (Example 1)

[0059] A negative electrode active material composed of hard carbon (BELLFINE manufactured by AT ELECTRODE, average particle size D50 = 1 μm) was used as the electrode active material. The electrode active material and sodium silicate aqueous solution (manufactured by Kanto Chemical Co., Ltd.: 36.6% (in terms of SiO2) (G) / 17.5% (in terms of Na2O)) were measured in a mass ratio of 91:9. The hard carbon powder in the mixed solution was used as a solid, and ion exchange water was added dropwise to make the solid concentration 60%. The mixture was mixed using a rotation and revolution mixer (Degassing Rentaro manufactured by THINKY) to obtain a slurry.

[0060] The slurry was applied to a diaphragm layer composed of a 0.1 mm thick β″-alumina solid electrolyte in such a way that the thickness after drying became 30 μm. After coating, the slurry was vacuum dried at 150° C. for 2 hours to solidify the sodium silicate and form an electrode (negative electrode) on the diaphragm layer.

[0061] A 500nm thick aluminum vapor-deposited film was formed on the surface of the electrode as a current collector. Then, in an argon glove box, metallic sodium was pasted on the separator layer in a facing manner as the opposite pole and sealed in a CR2032 button cell to prepare an all-solid-state battery.

[0062] For the prepared all-solid-state battery, a constant current charge and discharge test was carried out in a constant temperature chamber at 60°C with a current value of 0.02C rate (50 hours of charge and discharge). The charge and discharge were carried out with a termination voltage of 2.5 to 0.001V, and the charge and discharge efficiency was calculated based on the charge capacity and discharge capacity. The results are shown in Table 1.

[0063] (Example 2)

[0064] An all-solid-state battery was prepared in the same manner as in Example 1, except that a negative electrode active material composed of hard carbon (average particle size D50=10 μm) was used as the electrode active material and the electrode active material and the sodium silicate aqueous solution were measured at a mass ratio of 95:5, and the battery characteristics were evaluated. The results are shown in Table 1.

[0065] (Example 3)

[0066] An all-solid-state battery was prepared in the same manner as in Example 1, except that a negative electrode active material composed of hard carbon (average particle size D50=10 μm) was used as the electrode active material and the electrode active material and the sodium silicate aqueous solution were measured at a mass ratio of 97:3, and the battery characteristics were evaluated. The results are shown in Table 1.

[0067] (Example 4)

[0068] A negative electrode active material composed of metallic tin (manufactured by EM Japan, average particle size D50 = 0.5 μm) was used as the electrode active material, and the electrode active material and the sodium silicate aqueous solution were measured at a mass ratio of 87:13. Except for this, an all-solid-state battery was prepared in the same manner as in Example 1, and the battery characteristics were evaluated. The results are shown in Table 1.

[0069] (Example 5)

[0070] An all-solid-state battery was prepared in the same manner as in Example 1 except that the electrode active material and the sodium silicate aqueous solution were measured at a mass ratio of 70:30, and the battery characteristics were evaluated. The results are shown in Table 1.

[0071] (Example 6)

[0072] A positive electrode active material composed of Na3Fe2(PO4)P2O7 (average particle size D50 = 2 μm) was used as the electrode active material, and the electrode active material, sodium silicate aqueous solution, and carbon nanotubes were measured at a mass ratio of 94:5:1. An all-solid-state battery was prepared in the same manner as in Example 1. The battery characteristics were evaluated in the same manner as in Example 1 except that the battery was charged and discharged at a termination voltage of 4.5 to 1.5 V. The results are shown in Table 2.

[0073] (Example 7)

[0074] A positive electrode active material composed of Na2FeP2O7 (average particle size D50 = 0.7 μm) was used as the electrode active material, and the electrode active material, sodium silicate aqueous solution, and carbon nanotubes were measured at a mass ratio of 94:5:1. An all-solid-state battery was prepared in the same manner as in Example 1. The battery characteristics were evaluated in the same manner as in Example 1 except that the battery was charged and discharged at a termination voltage of 4.5 to 1.5 V. The results are shown in Table 2.

[0075] (Example 8)

[0076] A positive electrode active material composed of Na4Mn3(PO4)2P2O7 (average particle size D50 = 0.6 μm) was used as the electrode active material, and the electrode active material, sodium silicate aqueous solution, and carbon nanotubes were measured at a mass ratio of 94:5:1. An all-solid-state battery was prepared in the same manner as in Example 1. The battery characteristics were evaluated in the same manner as in Example 1 except that the battery was charged and discharged at a termination voltage of 4.5 to 1.5 V. The results are shown in Table 2.

[0077] (Comparative Example 1)

[0078] An all-solid-state battery was prepared in the same manner as in Example 1 except that sodium silicate was not added, and the battery characteristics were evaluated. The results are shown in Table 2.

[0079] (Comparative Example 2)

[0080] A negative electrode active material composed of hard carbon (BELLFINE manufactured by AT ELECTRODE, average particle size D50 = 1 μm) was used as the electrode active material, and Na3Zr2Si2PO 12 A solid electrolyte (average particle size D50 = 2 μm) was used instead of sodium silicate, and the electrode active material: solid electrolyte was measured at a mass ratio of 80:20. An all-solid-state battery was prepared in the same manner as in Example 1, and the battery characteristics were evaluated. The results are shown in Table 2.

[0081] Figure 3 A cross-sectional SEM image of the electrode formed on the separator layer in Example 1 is shown. Figure 4 The first charge and discharge curve of the test battery prepared in Example 1 is shown. In addition, Tables 1 and 2 show the results of the charge capacity, discharge capacity, and first charge and discharge efficiency of the test batteries prepared in Examples 1 to 8 and Comparative Examples 1 and 2.

[0082] [Table 1]

[0083]

[0084] [Table 2]

[0085]

[0086] like Figure 3 As shown, the dense electrode is closely (closely) formed on the diaphragm layer. As shown in Tables 1 and 2, the charging capacity is 87 mAh / g or more in Examples 1 to 8, but less than 1.3 mAh / g in Comparative Examples 1 and 2, and the performance is poor. In addition, the discharge capacity is 79 mAh / g or more in Examples 1 to 8, but less than 0.3 mAh / g in Comparative Examples 1 and 2, and the performance is poor. Regarding the first charge and discharge efficiency, it is 63.4% or more in Examples 1 to 8, but less than 23.1% in Comparative Examples 1 and 2, and the performance is poor.

[0087] Industrial Applicability

[0088] The solid electrolyte of the present invention is suitable for manufacturing sodium ion secondary batteries used in portable electronic devices, electric vehicles, electric tools, backup emergency power supplies, etc.

Claims

1. A solid electrolyte for a sodium ion secondary battery, characterized in that It contains alkali metal oxide and silicon oxide and is amorphous.

2. The solid electrolyte for sodium ion secondary battery according to claim 1, characterized in that In terms of mole %, it contains 5 to 70% Na2O and 15 to 90% SiO2.

3. The solid electrolyte for sodium ion secondary battery according to claim 1 or 2, characterized in that: Used in all-solid-state sodium-ion secondary batteries.

4. An electrode for a sodium ion secondary battery, characterized in that , The invention comprises the solid electrolyte for sodium ion secondary battery according to claim 1 or 2 and an electrode active material.

5. The electrode for sodium ion secondary battery according to claim 4, characterized in that: It also contains at least one sodium ion conductive crystal selected from the group consisting of β-alumina, β″-alumina and NASICON crystal.

6. The electrode for sodium ion secondary battery according to claim 4, characterized in that: The solid electrolyte for a sodium ion secondary battery is contained in the interior of the electrode for a sodium ion secondary battery.

7. The electrode for sodium ion secondary battery according to claim 4, characterized in that: The solid electrolyte for sodium ion secondary batteries is formed on one main surface of the electrode for sodium ion secondary batteries.

8. The electrode for sodium ion secondary battery according to claim 4, characterized in that: The electrode active material is a negative electrode active material.

9. The electrode for sodium ion secondary battery according to claim 8, characterized in that: The negative electrode active material contains: at least one metal crystal selected from Sn, Bi, Pb, P and Sb, an alloy crystal containing at least one selected from Sn, Bi, Pb, P and Sb, glass containing at least one selected from Sn, Bi and Sb, hard carbon or soft carbon.

10. The electrode for sodium ion secondary battery according to claim 4, characterized in that: The electrode active material is a positive electrode active material.

11. The electrode for sodium ion secondary battery according to claim 10, characterized in that: The positive electrode active material contains: (i) at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr, (ii) an element consisting of Na, and (iii) an element consisting of O.

12. The electrode for sodium ion secondary battery according to claim 10, characterized in that: The positive electrode active material contains a general formula of Na x M y P2O z A crystal represented by, wherein 1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, and M is at least one transition metal element selected from the group consisting of Fe, Mn, Co, Ni, V, Ti and Cr.

13. The electrode for sodium ion secondary battery according to claim 12, characterized in that: The positive electrode active material further contains an amorphous phase.

14. The electrode for sodium ion secondary battery according to claim 4, characterized in that: Also contains conductive additives.

15. The electrode for sodium ion secondary battery according to claim 4, characterized in that: The electrode active material and the solid electrolyte for sodium ion secondary batteries are contained in an amount of 70% to 99% by mass.

16. An all-solid-state sodium ion secondary battery, characterized in that: The invention comprises the electrode for a sodium ion secondary battery according to claim 4.

17. An all-solid-state sodium ion secondary battery, characterized in that: The invention comprises a solid electrolyte layer, wherein the solid electrolyte layer comprises the solid electrolyte for a sodium ion secondary battery according to claim 1 or 2.

18. A method for manufacturing an all-solid-state sodium ion secondary battery, characterized in that: include: A composite material coating step of coating an electrode composite material containing an electrode active material and water glass on a main surface of a diaphragm layer containing β-alumina, β″-alumina, and NASICON crystals; and The heat treatment step is to perform heat treatment at a temperature below 200°C after coating.

Citation Information

Patent Citations

  • All-solid-state sodium ion secondary battery

    WO2018225494A1